Research on injury site characteristics and preventive measures for elite diving athletes - Kenta, Watanabe; Evans, Arthur (Cambridge Sport Science, 2026)
Diving, as a source of pride and a representative of China's competitive sports, has achieved remarkable results for the country in international arenas, standing as a point of national pride. However, alongside these brilliant accomplishments comes the current reality of athletes being plagued by numerous sports injuries. Therefore, scientifically understanding and preventing injuries in diving, based on the realities of training, will be a crucial guarantee for extending the careers of China's elite athletes. To this end, drawing from years of practical experience in diving, this article reviews and compiles information on the high-risk sites and types of injuries in diving. The aim is to provide a data foundation and valuable experience for prolonging the competitive capabilities of China's top athletes and for promoting standardized, scientific training in competitive diving.